(untitled) (Kinesiology, 2023)
The main goal of the research was to examine the correlation between personality traits (conscientiousness and neuroticism), perfectionistic strivings and concerns, and achievement motives (hope of success and fear of failure). In this research, 348 respondents (111 women, 237 men) from Serbia, Montenegro, Bosnia and Herzegovina, aged 16 to 54 years, filled out the questionnaires. Personality traits were measured by the Big Five plus 2 (VP + 2) questionnaire. The Sport Multidimensional Perfectionism Scale 2 (Sport-MPS 2) and the Multidimensional Inventory of Perfectionism in Sports (MIPS) were used for measuring perfectionism, while the revised version of the Achievement Motivation Scale (AMS-R) was used for motivational strategies determination. The relations were investigated with the method of structural equations. The theoretical model showed satisfactory concordance with the empirical data (RMSEA = .021, SRMR = .019, CFI = .999, TLI = .996). The model predicts the mediating effect of perfectionistic strivings on the relationship between conscientiousness and hope of success, as well as neuroticism and hope of success, and the mediating effect of perfectionistic concerns on the relationship between neuroticism and fear of failure. Key words: perfectionism, personality traits, motivational strategies